Electrical properties of mismatched interface between InP and GaP - Li, G.-H.; Sun, Y.-N.; Yulius, A.; Broadbridge, C.C.; Woodall, J.M. (Rengong Jingti Xuebao/Journal of Synthetic Crystals, 2007)
The electrical properties of the mismatched interface between InP and GaP have been investigatedted. High resolution transmission electron microscopy (HRTEM) image shows the presence of strain relieving, 90° misfit dislocations at the InP/GaP interface. Electrochemical capacitance voltage (ECV) profiling indicates the presence of a high-density sheet of carriers at the interface. AFM image shows a pretty good InP epitaxial layer with surface roughness of 2.48 nm has been obtained. A model based on Fermi-level pinning in InP at the interface by misfit dislocations is proposed to account for the observed electrical behavior.
Keywords: Dislocations; InP/GaP interface; Lattice mismatch; dept.phy; ⛔ No DOI found

Normalized change - Marx, J.D.; Cummings, K. (American Journal of Physics, 2007)
Discussions of diagnostic tools that gauge students' conceptual understanding permeate the literature. Many instructors report their class' normalized gain to characterize the change in scores from pre-test to post-test. We describe a new procedure for characterizing these changes. This procedure, which we call the normalized change, c, involves the ratio of the gain to the maximum possible gain or the loss to the maximum possible loss. We also advocate reporting the average of a class' normalized changes and utilizing a particular statistical and graphical approach for comparing average c values. © 2007 American Association of Physics Teachers.
155 citations (Crossref) [2023-10-31]
Keywords: dept.phy

The stellar mass spectrum of the open cluster NGC 3293 - Slawson, R.W.; Ninkov, Z.; Horch, E.P. (Astrophysics and Space Science, 2007)
We have obtained and analyzed UBVRI CCD frames of the young, 4-10 Myr, open cluster NGC 3293 and the surrounding field in order to study its stellar content and determine the cluster's IMF. We found significantly fewer lower mass stars, M≤2.5M ⊙, than expected. This is particularly so if a single age for the cluster of 4.6 Myr is adopted as derived from fitting evolutionary models to the upper main sequence. Some intermediate-mass stars near the main sequence in the HR diagram imply an age for the cluster of about 10 Myr. When compared with the Scalo (The stellar initial mass function. ASP conference series, vol. 24, p. 201, 1998) IMF scaled to the cluster IMF in the intermediate mass range, 2.5≤M/M ⊙≤8.0 where there is good agreement, the high mass stars have a distinctly flatter IMF, indicating an over abundance of these stars, and there is a sharp turnover in the distribution at lower masses. The radial density distribution of cluster stars in the massive and intermediate mass regimes indicate that these stars are more concentrated to the cluster core whereas the lower-mass stars show little concentration. We suggest that this is evidence supporting the formation of massive stars through accretion and/or coagulation processes in denser cluster cores at the expense of the lower mass proto-stars. © 2007 Springer Science+Business Media B.V.
3 citations (Crossref) [2023-10-31]
Keywords: Mass function; Open clusters and associations: individual (NGC 3292); Stars: luminosity function; dept.phy

Ill-behaved convergence of a model of the Gd3Ga5O12 garnet antiferromagnet with truncated magnetic dipole?dipole interactions - Yavors'kii, T.; Gingras, Michel J. P.; Enjalran, Matthew (Journal of Physics: Condensed Matter, 2007)
Previous studies have found that calculations which consider long-range magnetic dipolar interactions truncated at a finite cut-off distance R c predict spurious (unphysical) long-range ordered phases for Ising and Heisenberg systems on the pyrochlore lattice. In this paper we show that, similar to these two cases, calculations that use truncated dipolar interactions to model the Gd3Ga5O12 garnet antiferromagnet also predict unphysical phases with incommensurate ordering wavevector q ord that is very sensitive to the dipolar cut-off distance R c. © IOP Publishing Ltd.
6 citations (Crossref) [2023-10-31] Citation Key Alias: pop00283 tex.type: [object Object]
Keywords: Antiferromagnetic materials; Crystal lattices; Finite cut off distance; Gadolinium compounds; Garnets; Heisenberg systems; Magnetic dipolar interactions; Magnetic moments; Numerical methods; Wavevector; dept.phy

A partnership inspiring interest in MSE careers: the center for research on interface structures and phenomena (CRISP) - Caragianis-Broadbridge, Christine; Edgecumbe, Heather; Osenko, Greg; Lehman, Ann; Alter, Lisa; Tully, John C (MRS Proceedings, 2007)
The intent of the CRISP education and outreach effort is to use materials science as a vehicle for enhancing the scientific literacy and knowledge of kindergarten through postgraduate level students. A challenging part of our mission has been inspiring students to take the next step and consider further study (or a career) in the field of Materials Science and Engineering (MSE). The CRISP educational programs were developed through a partnership between Yale University, Southern Connecticut State University and the urban school district of New Haven, CT. An overview of the methods and results of both formal and informal educational program components is included for years one and two of the CRISP MRSEC. This paper will focus on two CRISP programs: 1) MRSEC Initiative for Multidisciplinary Education & Research (MIMER) and 2) "Exploring Materials Science" mobile kits. The evaluation data indicates that the approach used in developing these educational programs is important. Specifically, the impact of these programs is influenced by the students' ability to relate the acquired knowledge to real life applications and technologies. In particular, emphasizing career opportunities rather than just presenting content-based programs is a key element to increasing interest towards further study in Materials Science and Engineering. © 2008 Materials Research Society.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/131-870-031-945-517 tex.type: [object Object]
Keywords: Career opportunities; Connecticut; Content-based; Educational program; Engineering education; Interface structures; Key elements; Materials; Materials science and engineering; Multidisciplinary education; Post-graduate levels; Professional aspects; Real-life applications; Scientific literacy; Students; Teaching; Urban schools; Yale University; dept.phy

The effectiveness of incorporating conceptual writing assignments into physics instruction - Cummings, Karen; Murphy, Michael (AIP Conference Proceedings, 2007)
This preliminary study examines the impact of conceptual writing assignments on student understanding of two physics concepts. Writing assignments covered the concepts of Newton's Third Law and the impulse-momentum relationship and were given to students in both high school and college level introductory physics classes. The students in these classes along with students in classes taught in an identical fashion by the same instructors without the addition of writing assignments were tested on their conceptual understanding of the two content areas. The results of this initial study indicate that the efficacy of this approach varied with topic. This study further indicates that students' benefit from the writing assignments was independent of their writing ability. © 2007 American Institute of Physics.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/168-392-262-279-442, pop00249 tex.number: [object Object]
Keywords: College; Conceptual learning; High school; Writing; dept.phy

Publishing and refereeing papers in physics education research - Hsu, Leon; Beichner, Robert J; Cummings, Karen; Kolodner, Janet L; Mccullough, Laura (Conference Cognitive Science, 2007)
At the 2007 Physics Education Research Conference, a workshop on publishing and refereeing was held with a panel of editors from four different publishing venues: the physics education research section of the American Journal of Physics, the Journal of the Learning Sciences, Physical Review Special Topics - Physics Education Research, and the Physics Education Research Conference Proceedings. These editors answered questions from participants regarding publishing in their respective venues, as well as writing referee reports that would be useful to both journal editors and authors. This paper summarizes the discussion. © 2007 American Institute of Physics.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Conference proceedings; Journals; Publishing; Referee reports; dept.phy

What factors really influence shifts in students’ attitudes and expectations in an introductory physics course? - Marx, Jeffrey; Cummings, Karen (2006 Physics Education Research Conference, 2007)
To gauge the impact of instruction on students' general expectations about physics and their attitudes about problem solving, we administered two different, but related, survey instruments to students in the first semester of introductory, calculus-based physics at McDaniel College. The surveys we used were the Maryland Physics Expectation Survey (MPEX) and the Attitudes about Problem Solving Survey (APSS). We found that the McDaniel College students' overall responses were more "expert-like" post-instruction: on the MPEX, the students' Overall agree/disagree score started at 59/18 and ended at 63/17, and on the APSS, the students' agreement-score went from 63 to 79. (All scores are out of 100%.) All of the students to whom we administered the MPEX and a significant sub-group to whom we administered the APSS realized these improvements without experiencing any explicit instructional intervention in this course aimed toward improving attitudes and expectations. These results contrast much of the previously reported findings in this area. © 2007 American Institute of Physics.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/005-519-377-568-644 tex.number: [object Object]
Keywords: dept.phy

Characterization of nanoparticles by computer imaging particle analysis - DaPonte, J.; Sadowski, T.; Broadbridge, C. C.; Munhutu, P.; Lehman, A.; Krishnamoorthy, D.; Garcia, E. C.; Sawicki, M. S.; Heyden, C.; Mirabelle, L.; Benjamin, P. (Nanomaterials Synthesis, Interfacing, and Integrating in Devices, Circuits, and Systems II, 2007)
Nanoparticles, particles with a diameter of 1-100 nanometers (nm), are of interest in many applications including device fabrication, quantum computing, and sensing because their decreased size may give rise to certain properties that are very different from those exhibited by bulk materials. Further advancement of nanotechnology cannot be realized without an increased understanding of nanoparticle properties such as size (diameter) and size distribution. Frequently, these parameters are evaluated using numerous imaging modalities including transmission electron microscopy (TEM) and atomic force microscopy (AFM). In the past, these parameters have been obtained from digitized images by manually measuring and counting many of these nanoparticles, a task that is highly subjective and labor intensive. Recently, computer imaging particle analysis routines that count and measure objects in a binary image^1 have emerged as an objective and rapid alternative to manual techniques. In this paper a procedure is described that can be used to preprocess a set of gray scale images so that they are correctly thresholded into binary images prior to a particle analysis ultimately resulting in a more accurate assessment of the size and frequency (size distribution) of nanoparticles. Particle analysis was performed on two types of calibration samples imaged using AFM and TEM. Additionally, results of particle analysis can be used for identifying and removing small noise particles from the image. This filtering technique is based on identifying the location of small particles in the binary image, assessing their size, and removing them without affecting the size of other larger particles.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/032-875-618-829-762, pop00276
Keywords: Atomic force microscopy; Bulk materials; Computer imaging; Device fabrication; Imaging techniques; Nanoparticles; Particle analysis; Quantum computers; Size distribution; Thresholding; Transmission electron microscopy; dept.csc; dept.phy

Application of particle analysis to transmission electron microscopy (TEM) - Daponte, John S; Sadowski, Thomas; Broadbridge, Christine; Day, D; Lehman, A; Krishna, D; Marinella, L; Munhutu, P; Sawicki, M (Visual Information Processing Conference, 2007)
Nanoparticles, particles with a diameter of 1-100 nanometers (nm), are of interest in many applications including device fabrication, quantum computing, and sensing because their size may give them properties that are very different from bulk materials. Further advancement of nanotechnology cannot be obtained without an increased understanding of nanoparticle properties such as size (diameter) and size distribution frequently evaluated using transmission electron microscopy (TEM). In the past, these parameters have been obtained from digitized TEM images by manually measuring and counting many of these nanoparticles, a task that is highly subjective and labor intensive. More recently, computer imaging particle analysis has emerged as an objective alternative by counting and measuring objects in a binary image. This paper will describe the procedures used to preprocess a set of gray scale TEM images so that they could be correctly thresholded into binary images. This allows for a more accurate assessment of the size and frequency (size distribution) of nanoparticles. Several preprocessing methods including pseudo flat field correction and rolling ball background correction were investigated with the rolling ball algorithm yielding the best results. Examples of particle analysis will be presented for different types of materials and different magnifications. In addition, a method based on the results of particle analysis for identifying and removing small noise particles will be discussed. This filtering technique is based on identifying the location of small particles in the binary image and removing them without affecting the size of other larger particles.
1 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Computer imaging; Flat field correction; Flat field correction and rolling ball background correction; Imaging particle analysis; Imaging systems; Magnification; Microfabrication; Nanoparticles; Nanotechnology; Quantum computers; Rolling ball background correction; Size distribution; Transmission electron microscopy; dept.csc; dept.phy

Comparison of thresholding techniques on nanoparticle images - Daponte, John S; Sadowski, Thomas; Broadbridge, Christine; Day, D; Lehman, A; Krishna, D; Marinella, L; Munhutu, P; Sawicki, M (Visual Information Processing Conference, 2007)
Thresholding is an image processing procedure used to convert an image consisting of gray level pixels into a black and white binary image. One application of thresholding is particle analysis. Once foreground objects are separated from the background, a quantitative analysis that characterizes the number, size and shape of particles is obtained which can then be used to evaluate a series of nanoparticle samples. Numerous thresholding techniques exist differing primarily in how they deal with variations in noise, illumination and contrast. In this paper, several popular thresholding algorithms are qualitatively and quantitatively evaluated on transmission electron microscopy (TEM) and atomic force microscopy (AFM) images. Initially, six thresholding algorithms were investigated: Otsu, Riddler-Calvard, Kittler, Entropy, Tsai and Maximum Likelihood. The Riddler-Calvard algorithm was not included in the quantitative analysis because it did not produce acceptable qualitative results for the images in the series. Two quantitative measures were used to evaluate these algorithms. One is based on comparing object area the other on diameter before and after thresholding. For AFM images the Kittler algorithm yielded the best results followed by the Entropy and Maximum Likelihood techniques. The Tsai algorithm yielded the top results for TEM images followed by the Entropy and Kittler methods.
2 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Algorithms; Atomic force microscopy; Binary images; Maximum likelihood; Nanoparticle; Nanoparticle samples; Nanoparticles; Pixels; Riddler-Calvard algorithm; Thresholding; Transmission electron microscopy; Tsai algorithm; dept.csc; dept.phy